Abnormal left ventricular geometry in female collegiate swimmers. (14th October 2021) - Taha, Y K; Rambart, C A; Reifsteck, F; Hamburger, R; Clugston, J R; Handberg, E M; Street, J; Dasa, O; Pepine, C J; Martinez, M; Edenfield, K M
Abstract: Background: There is a paucity of data describing left ventricular geometry changes in female athletes. While some studies suggest that female athletes participating in dynamic sports exhibit higher prevalence of eccentric left ventricular hypertrophy (LVH) when compared to men, a recent study suggested more concentric geometry changes in female basketball athletes. We were unable to identify studies describing the left ventricular geometry of female collegiate swimmers. Objectives: To describe LV geometry changes in a cohort of female collegiate swimmers. Methods: We analyzed a cohort of female collegiate swimmers who had a pre-participation cardiac evaluation by 12-lead ECG and 2-dimensional echocardiography. Left ventricular (LV) geometry was assessed based on relative wall thickness (RWT) (defined as: 2 x posterior wall thickness (PWT) divided by LV end-diastolic diameter (LVEDD)) and LV mass (LVM) (Devereux's formula: LVM = [0.8 x 1.04 [(LVEDD + interventricular septum + posterior wall thickness)3 − (LVEDD)3]] + 0.6g) and was indexed to body surface area (BSA).LVH was defined as LV mass index >95 g and was defined as concentric when associated with a relative wall thickness (RWT) >0.42 and as eccentric when RWT was ≤0.42. Concentric remodeling was defined as normal LVM index and increased RWT. Results: A total of 83 female collegiate swimmers were included. Their age was 18.5±0.5 years (mean ± standard deviation, SD), 74 (89.2%) were White, BSA was 1.78±0.11 m 2, height 173±6.3 cm, weight 66.2±7.2 K. Their interventricular septum diameter was 0.89±0.14 cm, PWT 0.92±0.15 cm, LVEDD 4.9±0.5 cm and LV end-systolic diameter (LVESD) 3.2±0.4 cm. Left atrium diameter ranged from 2.6 to 4.3 cm (mean 3.4 cm ± 0.4 cm). Aortic root diameter ranged from 1.9 to 3.5 cm (mean 2.7±0.3 cm) (Figure 1). LVH was present in 27 swimmers (32.5%). Eccentric LVH was present in 17 athletes (20.5%), concentric hypertrophy in 10 athletes (12%), and concentric remodeling in 12 (14.5%) (Figure 2). No athletes with LVH or concentric remodeling had borderline or abnormal ECG findings based on international criteria. Only two women with normal LV geometry had abnormal ECG findings: prolonged QT interval and abnormal T wave inversion. There was a linear correlation between BSA with LVEDD, LVESD and LV mass (r=0.40, 0.35, and 0.48 with P<0.001, 0.002 and <0.001, respectively). However, there was no statistically significant difference between LV geometry groups based on BSA or blood pressure. Conclusion: Our data document a high incidence of eccentric hypertrophy among female collegiate swimmers. Concentric remodeling and hypertrophy were also relatively high. Differentiating physiologic from pathologic cardiac remodeling in these athletes is critical to prevent potential complications such as sudden cardiac death, arrhythmias, and other adverse outcomes. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): This work was supported in part by the American Medical Society for Sports Medicine (AMSSM) Foundation Research Grant 2016 awarded to KE, and the University of Florida REDCap uses the NIH National Center for Advancing Translational Sciences (NCATS) grant UL1 TR001427.